The other side of polyandry : property, stratification, and nonmarriage in the Nepal Himalayas - Schuler, Sidney (Women in cross-cultural perspective., 2019)
This book provides demographic data on polyandry and nonmarriage, exploring the social and economic context of nonmarriage and its implications vis-a-vis the position of women in the Nepal. It fills gaps in the literature on Tibetan societies with respect to stratification and the position of women.